Tumor Size, an Additional Risk Factor of Local Recurrence in Low-Risk Endometrial Cancer: A Large Multicentric Retrospective Study. Issue 4 (1st May 2018) - Sozzi, Giulio; Uccella, Stefano; Berretta, Roberto; Petrillo, Marco; Fanfani, Francesco; Monterossi, Giorgia; Ghizzoni, Viola; Frusca, Tiziana; Ghezzi, Fabio; Chiantera, Vito; Scambia, Giovanni
Abstract : Objective: The identification of patients with endometrial cancer (EC) at higher risk for relapse is critical to individualize and better tailor postoperative treatment. No evidence is available regarding the possible association between tumor size (TS) and the risk of local recurrence. The purpose of this study was to analyze the correlation between TS and risk/type of recurrence in EC patients, stratified according to the new European Society of Medical Oncology-European Society of Gynecological Oncology-European Society for Radiotherapy and Oncology classification. Methods: Data of patients with histologically proven EC who received primary surgical treatment between November 1999 and June 2015 were retrospectively retrieved from 5 institutions. Optimal TS cutoff was calculated using a receiver operating characteristic curve. Site of recurrence as a function of TS and groups of risk were analyzed. Local recurrence-free survival, recurrence-free survival, and overall survival were calculated using the Kaplan-Meier method. Results: Data of 1166 patients were analyzed. Among them, 514 (44.1%) had low-risk EC, 174 (14.9%) had intermediate risk EC, 173 (14.8%) had high–intermediate risk EC, and 305 (26.2%) had high-risk EC. A total of 134 (11.5%) women had recurrence: 47 (4%) of them had local relapse, 30 (2.6%) had locoregional relapse, and 57 (4.9%) had distant relapse. Tumor size 25 mm or greater emerged as the threshold for the prediction of a higher rate of local recurrence ( P < 0.0001, hazard ratio = 18.2, P = 0.005) and a lower local recurrence-free survival and recurrence-free survival ( P < 0.0001) only in patients with low-risk EC. There was no statistically significant correlation between TS and recurrence in the other risk groups. Conclusions: In this very large series, tumor size emerges as an independent prognostic factor of local recurrence in women with low-risk EC and could be a valuable additional criterion to personalize the treatment approach to these patients.